1990
DOI: 10.1016/0017-9310(90)90039-w
|View full text |Cite
|
Sign up to set email alerts
|

Etude expérimentale de la convection mixte entre deux plans horizontaux à températures différentes—II

Abstract: R d _ ésum appanll � n Une de la con investigatio vecllon ? mixte expérimentale sous par forme de anémométrie rouleaux laser est transversaux réalisée ou pour longitudinaux déterminer les dans un conditions canal rectangulaire. Les expene � ces sont eff ectuées pour des nombres de Reynolds Re et des nombres de Rayleigh Ra dans le domaine 0,03 � Re� 3.3 et Ra� 4700, utilisant l'eau comme fluide d'étude. EXPERIMENTAL STUDY OF MIXED CONVECTION BETWEEN TWO HORIZONTAL PLATES AT DIFFERENT TEMPERATURES-Il Abstract-La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 21 publications
(11 reference statements)
6
27
0
1
Order By: Relevance
“…Similar patterns also appear in the Taylor-Couette system with an axial throughfiow [21,22]. In recent experimental work on Rayleigh-Benard convection with throughffow competition between longitudinal and transversal rolls [13,23] has been observed; also a superposition of both structures and more complicated timedependent behavior is possible. This competitive dynamics has been investigated by Brand, Ahlers, and Deissler [24] with a phenomenological model of two coupled amplitude equations for transversal and longitudinal rolls which, however, di6'er from the more rigorously derived equations [25].…”
Section: Introductionmentioning
confidence: 55%
“…Similar patterns also appear in the Taylor-Couette system with an axial throughfiow [21,22]. In recent experimental work on Rayleigh-Benard convection with throughffow competition between longitudinal and transversal rolls [13,23] has been observed; also a superposition of both structures and more complicated timedependent behavior is possible. This competitive dynamics has been investigated by Brand, Ahlers, and Deissler [24] with a phenomenological model of two coupled amplitude equations for transversal and longitudinal rolls which, however, di6'er from the more rigorously derived equations [25].…”
Section: Introductionmentioning
confidence: 55%
“…Later on, Luijkx et al 9 have demonstrated the existence of transverse rolls parallel to the flow direction for which the critical Rayleigh number increases when Reynolds number increases. Several experimental and numerical investigations were carried out to determine the conditions of transverse roll onset in a rectangular channel 3,10,11 . They also proved that the critical Rayleigh number of the appearance of the transverse rolls depends on the Prandtl number and the aspect ratio of the channel.…”
Section: Introductionmentioning
confidence: 97%
“…Thus the stability diagrams of PRB flows present many flow configurations. A few examples, established experimentally, theoretically and numerically, for different Prandtl numbers and aspect ratios, can be found in [6][7][8][9] in the case of pure fluids. In the case of air PRB flows (Pr=0.7), a complete stability diagram at B≥10 is presented in [10].…”
Section: Introductionmentioning
confidence: 99%